The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1017/jfm.2021.772
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation of a thin droplet in a shallow well: theory and experiment

Abstract: Motivated by the industrial manufacture of organic light-emitting-diode displays, we formulate and analyse a mathematical model for the evolution of a thin droplet in a shallow axisymmetric well of rather general shape both before and after touchdown that accounts for the spatially non-uniform evaporation of the fluid, perform physical experiments using three cylindrical wells with different small aspect ratios, and validate the mathematical model by comparing the present experimental results with the correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…On the other hand, a few theoretical investigations of evaporation of a droplet in a well have also been performed. D’Ambrosio et al formulated a mathematical model for the evolution of a thin droplet in a shallow axisymmetric well and validated the model by comparison with the present experimental results . Ahn et al used the level-set method to extend to three-dimensional computations of liquid film evaporation in circular and square microcavities and investigated the effects of dynamic contact angles and cavity geometry on the film evaporation …”
Section: Introductionmentioning
confidence: 67%
“…On the other hand, a few theoretical investigations of evaporation of a droplet in a well have also been performed. D’Ambrosio et al formulated a mathematical model for the evolution of a thin droplet in a shallow axisymmetric well and validated the model by comparison with the present experimental results . Ahn et al used the level-set method to extend to three-dimensional computations of liquid film evaporation in circular and square microcavities and investigated the effects of dynamic contact angles and cavity geometry on the film evaporation …”
Section: Introductionmentioning
confidence: 67%
“…2020; D'Ambrosio et al. 2021) and multiple interacting droplets (see for example Wray et al. 2020, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Deegan et al presented the deposition patterns of the evaporated droplet for a wide range of surfaces, solvents, and solutes. The evaporation phenomena of droplet and extreme modes of contact angle on a strongly hydrophobic substrates were discussed briefly by Stauber et al The comparison of theoretical predictions with the experimental results on variation of a thin droplet in a shallow well and the effect of non-uniform evaporation of the fluid were presented by Ambrosio et al Tomo et al reported the variation of ultrathin films in nanotubes with the addition of molecular interactions and balance of pressure variations in the formation of the meniscus in the ultrathin films. Also, there are several applications of the liquid bridges like many medical problems involving respiratory diseases, and the health of the body joints depends on liquid bridges .…”
Section: Introductionmentioning
confidence: 99%